Late Surgical Management Of A Rare Case Of Post-traumatic Orbital Encephalocele - Nepal, Yugal Jyoty; Shilpakar, Sushil Krishna; Sedain, Gopal; Shrestha, Dipendra Kumar (Nepal Journal of Neuroscience, 2019)
Orbital roof fractures after blunt head trauma are not uncommon. Hernia ion of the brain tissues into the orbit through a bony defect, so-called post-traumatic orbital encephalocele, is a rare entity. The herniated braint issue causes compression of the intraorbital contents, particularly the optic nerve, extraocular nerves and muscles and compromise the vascular supply. Raisedintraorbital pressure may lead to irreversible damage to the optic nerve. This can be prevented by early diagnosis and timely management. Repair of the orbital roof needs to be performed to avoid transmission of intracranial pressure into the orbit. Early intervention is needed in order to prevent visual loss. We present a case of posttraumatic orbital encephalocele who underwent latesurgical treatment with direct repair of dura opening, reinforcement with temporalis fascia and reconstruction of orbital roof using skull bone graft. Complete resolution of the pulsatile proptosis with excellent cosmetic result was observed at follow up. However, the visual diminution did not recover significantly due to late diagnosis and intervention. Early diagnosis and surgical management of this rare condition can prevent permanent visual loss and also achieve good cosmetic results.